Purification of Angiotensin-I-Converting Enzyme Inhibitory Peptides Derived from Camellia oleifera Abel Seed Meal Hydrolysate - Guang-long Yao; Wei He; You-gen Wu; Jian Chen; Xin-wen Hu; Jing Yu (Journal of Food Quality)
China is a large country that produces Camellia oleifera Abel seed meal (COASM), a by-product of tea-seed oil, which is only used as an organic fertilizer, resulting in a serious waste of high-quality resources. The preparation of the ACE inhibitory peptide from COASM and the study of its functional properties are of practical importance in improving the comprehensive utilization of COASM. Our manuscript presents an optimized preparation of ACE inhibitory peptides with alkaline protease and enzyme kinetics parameters. Ultrafiltration, gel chromatography, and RP-HPLC purification were conducted for ACE inhibitory peptides, and peptide molecular weight distribution and amino acid composition were analyzed in the enzymolysis liquid. The following were the conditions of the optimized enzymatic hydrolysis to obtain ACE inhibitory peptides from COASM: 15 times of hydrolysis in distilled water for 3.5 h at 50°C, pH = 8.5, substrate concentration of 17 mg/g, and addition of 6% (w/w) alkaline protease. Under this condition, the peptides produced exhibited an ACE inhibition rate of 79.24%, and the reaction kinetics parameters are as follows: Km = 0.152 mg/mL and Vmax = 0.130 mg/mL·min. The majority of ACE inhibitory peptides from COASM have molecular weight below 1 kDa, and a high ACE inhibitory rate was achieved after dextran gel chromatography separation and purification (whose IC50 was 0.678 mg/mL). The hydrophobic amino acid content in this fraction reached 51.21%.